Human haematopoietic stem/progenitor cells express several functional sex hormone receptors. Issue 1 (30th October 2015) - Abdelbaset‐Ismail, Ahmed; Suszynska, Malwina; Borkowska, Sylwia; Adamiak, Mateusz; Ratajczak, Janina; Kucia, Magda; Ratajczak, Mariusz Z.
Abstract: Evidence has accumulated that murine haematopoietic stem/progenitor cells (HSPCs) share several markers with the germline, a connection supported by recent reports that pituitary and gonadal sex hormones (SexHs) regulate development of murine HSPCs. It has also been reported that human HSPCs, like their murine counterparts, respond to certain SexHs ( e.g . androgens). However, to better address the effects of SexHs, particularly pituitary SexHs, on human haematopoiesis, we tested for expression of receptors for pituitary SexHs, including follicle‐stimulating hormone (FSH), luteinizing hormone (LH), and prolactin (PRL), as well as the receptors for gonadal SexHs, including progesterone, oestrogens, and androgen, on HSPCs purified from human umbilical cord blood (UCB) and peripheral blood (PB). We then tested the functionality of these receptors in ex vivo signal transduction studies and in vitro clonogenic assays. In parallel, we tested the effect of SexHs on human mesenchymal stromal cells (MSCs). Finally, based on our observation that at least some of the UCB‐derived, CD45 − very small embryonic‐like stem cells (VSELs) become specified into CD45 + HSPCs, we also evaluated the expression of pituitary and gonadal SexH receptors on these cells. We report for the first time that human HSPCs and VSELs, like their murine counterparts, express pituitary and gonadal SexH receptors at the mRNA and protein levels. Most importantly, SexH if added to suboptimal doses of haematopoietic cytokines and growth factors enhance clonogenic growth of human HSPCs as well as directly stimulate proliferation of MSCs.